The Effect of Knowledge on The Consumption of Fe Tablets in Adolescent Girls: Literature Review - Ratna Wulandari; Siti Hodijah (Sekolah Tinggi Ilmu Kesehatan Adila Bandar Lampung, 2026)
Prevention of anemia during pregnancy needs to be done since before pregnancy. Based on data from the Indonesian Health Survey in 2023, 15.5% of adolescents experience anemia, and 27.7% of pregnant women anemia. In this modern era, knowledge is easier to acquire, but the knowledge gained is not always applied as a good health habit. This study aims to determine the knowledge of adolescent girls in Indonesia about the prevention of anemia and its effect on the consumption of Fe tablets . The research was conducted by reviewing literature for the last 5 years of research, in 2021 - 2025 on Google Scholar. The search results obtained 24 articles that meet the criteria after extraction using Prisma Diagram. The results showed that having young women who have good knowledge has an effect on the consumption of Fe tablets regularly, but knowledge does not stand alone. Factors such as the media and methods of education, social support, personal motivation, as well as the role of health workers and teachers are also of great importance. Some young women remain disobedient despite their knowledge, which shows the importance of integrated and sustained intervention.